Picosecond stability of injection of parallel high-current pulsed electron beams; Technical Physics Letters; Vol. 35, № 9 - Yalandin M. I.; Reutova A. G.; Ul'maskulov M. R.; Sharypov K. A.; Shpak V. G.; Shunailov S. A.; Klimov A. I.; Rostov V. V.; Mesyats G. A. Gennady Andreyevich (2009, 2009)
В фонде НТБ ТПУ отсутствует